2015
DOI: 10.18632/oncotarget.6101
|View full text |Cite
|
Sign up to set email alerts
|

Beyond proliferation: KLF5 promotes angiogenesis of bladder cancer through directly regulating VEGFA transcription

Abstract: Abundant evidence has demonstrated critical roles of KLF5 in regulating cell proliferation in various cancers, however, its additional roles in other aspects of cancer development remain to be further clarified. In this study, we found that KLF5 was essential for cancer cell-endothelial cell interaction in vitro and tumor angiogenesis in nude mice based on lentivirus-mediated KLF5 knockdown bladder cancer cell models. Moreover, KLF5 insufficiency abolished the ability of bladder cancer cells to induce neovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 35 publications
5
46
0
Order By: Relevance
“…Therefore, a CNC network was built to further survey the relation of dyregulated lncRNAs and mRNAs. Some major connected mRNAs have been known to be associated with BC, such as VEGFA, PTEN, EGF and FGFR3 [2426]. We thus deduced that these lncRNAs might be correlated with carcinogenesis of BC by regulating co-expression genes.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, a CNC network was built to further survey the relation of dyregulated lncRNAs and mRNAs. Some major connected mRNAs have been known to be associated with BC, such as VEGFA, PTEN, EGF and FGFR3 [2426]. We thus deduced that these lncRNAs might be correlated with carcinogenesis of BC by regulating co-expression genes.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that KLF5 has a role in different cell processes, including in cell proliferation, cell cycle progression and apoptosis (9)(10)(11). Previous studies have demonstrated that KLF5 acts as an oncogene in different cancer cells, and is a potential tumor suppressor in prostate cancer cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…KLF5 expression in breast cancer exhibit shorter disease-free survival times, and increased KLF5 expression aids in cancer cell proliferation and tumorigenesis (10,12). However, KLF5 has also been demonstrated to act as a tumor suppressor under certain conditions, including JNK activation-induced apoptosis in esophageal squamous cell cancer (13).…”
Section: Klf5 Promotes Apoptosis Induced By Phorbol Ester As An Effecmentioning
confidence: 99%
See 2 more Smart Citations